Synthesis of 4-hydroxyquinoline-2(1H)-ones Based on Ag(I)-catalyzed Carbon Dioxide Fixation on 2-alknylanilines - Lin, Xin-Yu; Chen, Guo-Jun; Wu, Su-Zhe; Xu, Ke-Xuan; Zhang, Xiao-Tian; Feng, Qi (Letters in Organic Chemistry, 2025)
4-Hydroxyquinoline-2(1H)-ones exhibit multiple biological activities, and studying their synthetic methods is of great significance. In the presence of tetramethylguanidine and silver nitrate, 4-hydroxyquinoline-2(1H)-ones were efficiently synthesized from 2-ethynylanilines and carbon dioxide under atmospheric pressure. The reaction conditions, such as types of silver catalysts and reaction solvents, were optimized, and the applicability of the substrate was preliminarily investigated. This method provides an alternative pathway for the synthesis of 4-hydroxyquinoline-2(1H)-ones and the conversion and utilization of carbon dioxide.
Keywords: 4-Hydroxyquinoline-2(1H)–ones